Clinical Outcomes after Minimally Invasive Trans-Psoas Lateral Lumbar Interbody Fusion for the Treatment of Adult Degenerative Scoliosis: Four Years’ Multicenter Study - Sheikh Asad; Arjun Dubey; Arvind Dubey; Chester Sutterlin (Indian Journal of Neurosurgery)
The use of minimally invasive transpsoas lateral lumbar interbody fusion (LLIF) surgery for treatment of adult degenerative scoliosis is rapidly increasing in popularity. However, limited data is available regarding its use in adult degenerative lumbar scoliosis surgery. The objective of this study was to evaluate the clinical outcomes of adults with degenerative lumbar scoliosis who were treated with minimally invasive LLIF. Thirty-two consecutive patients with adult degenerative scoliosis treated by a single surgeon at two spine centers were followed up for an average of 13.2 months. Interbody fusion was completed using the minimally invasive LLIF technique with supplemental 360 degrees’ posterior instrumentation. Oswestry disability index (ODI) scores were obtained preoperatively and at most recent follow-up. Complications were recorded. The study group demonstrated improvement in clinical outcome scores. ODI scores improved from 36.8 to 23.4 (p < 0.00001). A total of four complications (12%) were recorded, and two patients (6%) required additional surgery. Based on the significant improvement in validated clinical outcome scores, minimally invasive LLIF can be considered an effective procedure in the treatment of adult degenerative scoliosis.